2013
DOI: 10.4038/seajme.v7i2.140
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception of problem-based learning conducted in phase1 medical program, UCSI University, Malaysia

Abstract: Problem-based learning (PBL) has been introduced in the Phase 1 curriculum of Doctor of Medicine programme at Faculty of Medicine & Health Sciences, UCSI University since its inception in 2005. The main objective of this study was to investigate the perception of medical students on problembased learning sessions. A cross sectional study was conducted on a total of 115 medical students from June 2011 to June 2012. Forty nine (42.6%), 31(27%) and 35(30.4%) medical students from first, second and third years res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Furthermore, previous a study indicated that PBL graduates rated themselves better prepared professionally than other non-PBL graduates regarding interpersonal abilities, problem-solving skills and the ability to work and plan efficiently and autonomously ( 2 ). In contrary, studies found that PBL requires much time that must be provided to solve complex problems, which lead to a lack of time available for the material/content ( 16 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous a study indicated that PBL graduates rated themselves better prepared professionally than other non-PBL graduates regarding interpersonal abilities, problem-solving skills and the ability to work and plan efficiently and autonomously ( 2 ). In contrary, studies found that PBL requires much time that must be provided to solve complex problems, which lead to a lack of time available for the material/content ( 16 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, a study by Emerald et al showed that PBL was time-consuming, and can be substituted by other instructional methods. 11 Students will remember more content if brief activities are introduced in the lecture, and in order to emphasize and maintain students individual responsibility, the entire course need not be team based. 12 Newman concluded that the limited high-quality evidence available from existing reviews does not provide robust evidence about the effectiveness of different kinds of PBL in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 However, a few studies reported that PBL as an instructional method is time consuming, and does not impact knowledge acquisition. 12 , 13 The tutors guide the group to achieve their goals by keeping them focused on their task. The PBL sessions involve clear roles for each member of the group, known steps of discussion, and identification of the learning objectives from the discussed problem.…”
mentioning
confidence: 99%
“…However, in Malaysia they showed that PBL was time consuming, and can be substituted by other instructional methods. 12 Therefore, the student’s impression of the PBL session is controversial. Thus, the current study was designed to investigate the student’s perception of PBL sessions in the College of Medicine, KSU, Riyadh, KSA.…”
mentioning
confidence: 99%